PENERAPAN ASAS RESIPROSITAS (TIMBAL BALIK) DALAM PROSES EKSTRADISI: STUDI KASUS MARIA LUMOWA - Komara, Stevani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Extradition is known as the process of sending a person who is a defendant or convict who has fled abroad to avoid punishment or trial proceedings. Extradition can be carried out on the basis that the two countries already have previous extradition treaties or based on the principle of reciprocity. It is not uncommon for a country to refuse to hand over a defendant to the applicant's country for various reasons. For example in the case of Maria Lumowa, a fugitive in the bank burglary case for 17 years who was finally extradited back to Indonesia from Serbia. The two countries have never previously entered into an extradition treaty. However, Serbia has a good intention to extradite Maria based on the historical closeness of the two countries' longstanding bilateral relations, as well as remuneration to Indonesia for granting Serbia's extradition request against the perpetrator of theft of customer data in 2015. It can be seen that extradition is not always about having an agreement in order to work, but also seeing the goodwill of the requested country.